Capturing CO2 from the atmosphere: Design and analysis of a large-scale DAC facility - Mahmoud Mostafa; Cristina Antonicelli; Christopher Varela; Diego Barletta; Edwin Zondervan (Carbon Capture Science & Technology, 2022)
Direct air carbon capture (DAC) technologies can substantially lower the CO2 concentrations in the atmosphere by enabling negative emissions. This study shows in detail the design of the DAC plant at industrial scale and provides insights on its performance in terms of process economic and CO2 emissions count. The proposed DAC plant is optimized to capture CO2 directly from the atmospheric air, employing a sensitivity analysis to find the influence of operation and design parameters on the total cost. Absorption using sodium hydroxide as chemisorbent is utilized with a capture rate of 0.7. Industrially mature common process units are considered to achieve a design that is relevant in the near future. An initial base case design indicates a carbon cost of 244 $/ton-CO2 with the operating expenses comprising 84% of the total cost. Then, two scenarios are proposed to enhance the process performance: heat integration and use of renewable energy. Through the heat integration, the carbon ratio (CO2 captured / CO2 emitted) improves from a value of 2.7 for the base case to 3.73, meaning less CO2 is emitted per captured amount due to lower fuel consumption. The resulting cost goes down to 125 $/ton-CO2, with two additional heat exchangers added to the network. Furthermore, renewable scenario is considered where a parallel electrolysis stage feeds the process hydrogen fuel and oxygen required for combustion in the calciner. This scenario indicates that higher operating costs are incurred due to the expensive green fuel. Finally, a profitability analysis is performed to establish the feasibility for further processing to methanol in a Power-to-X facility. The estimations indicate that the hydrogen price has to go down by 46.3% in order to break-even.